PKU BAGI GURU BK SMK KABUPATEN MAGELANG UNTUK OPTIMALISASI KOMPETENSI, KINERJA DAN LAYANAN GURU BK BERBASIS FLOP SMART - Putro, Hijrah Eko; Tawil, Tawil (UNIVERSITAS PGRI MADIUN, 2019)
Abstract. University partnership program aims to: (1) enhance the quality, performance and service teacher BK in the school environment; (2) Improving the competence of teachers BK in carrying out guidance and counseling services to students; (3) Increase of innovations in managing the administration of BK-based smart flop.University partnership program was conducted in the laboratory of the Faculty of Economics and business Internet Muhammadiyah University of Magelang, on December 13-14 March 2019. Trainees are teachers BK CMS in Magelang Regency. In order to achieve the goals that have been mentioned before, then taken steps as follows: (1) contact the headteacher and Chair of guidance counseling Teacher Magelang to know the extent to which teachers utilize smart looking and flop analysis data related training needed in increasing competence, service and performance teacher BK through the analysis of a smart flop; (2) organized a training program that includes the stage introduction, the training phase, and the phase of evaluation results; (3) the stage of introduction and training is done in groups.Based on the results of the University partnership program can be concluded: (1) this activity can improve the understanding and skill in the use of a smart flop analysis; (2) these activities are able to improve and optimize the performance of teacher competence, BK in providing guidance and counselling services in particular related patterns service BK to the students; (3) the activity is able to foster a spirit of improvements to independently by utilizing technology-based smart flop. Abstrak. Program kemitraan universitas ini bertujuan untuk: (1) Meningkatkan layanan, kinerja dan kualiatas guru BK di lingkungan sekolah; (2) Meningkatkan kompetensi guru BK dalam melaksanakan layanan bimbingan dan konseling kepada siswa; (3) Menambah inovasi dalam mengelola administrasi BK berbasis flop smart (from laptop to smartphone).Program kemitraan universitas ini dilaksanakan di Laboratorium Internet Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Magelang, pada tanggal 13-14 Maret 2019. Peserta pelatihan adalah guru BK SMK di Kabupaten Magelang. Dalam rangka mencapai tujuan yang telah disebutkan sebelumnya, maka ditempuh langkah-langkah sebagai berikut: (1) Menghubungi Kepala Sekolah dan Ketua Musyawarah Guru Bimbingan Konseling untuk mengetahui sejauh mana guru memanfaatkan analisis flop smart (from laptop to smartphone). dan mencari data terkait pelatihan yang dibutuhkan dalam peningkatan kompetensi, layanan dan kinerja guru BK melalui analisis flop smart (from laptop to smartphone); (2) Menyelenggarakan program pelatihan yang meliputi tahap pengenalan, tahap pelatihan, dan tahap evaluasi hasil; (3) Tahap pengenalan dan pelatihan dilakukan secara kelompok.Berdasarkan hasil program kemitraan universitas dapat disimpulkan: (1) Kegiatan ini dapat meningkatan pemahaman dan keterampilan dalam penggunaan analisis flop smart (from laptop to smartphone), (2) Kegiatan ini mampu meningkatan dan mengoptimalkan kompetensi, kinerja guru BK dalam memberikan layanan bimbingan dan konseling khususnya terkait pola pelayanan BK kepada siswa. (3) Kegiatan ini mampu menumbuhkan semangat dalam peningkatan kinerja secara mandiri dengan memanfaatkan teknologi berbasis flop smart (from laptop to smartphone).